Farmer’s Choice and Farmer’s Voice on the Use of Local versus Modern Inputs in Peri-Urban Agriculture in Kathmandu Valley, Nepal - Sapkota, Kanhaiya (Geographical Journal of Nepal, 2009)
Farmers’ knowledge and practices on local versus modern inputs on peri-urban agriculture were investigated by interviewing 20 vegetable growers with purposive sampling in the Manahara river basin of Kathmandu Valley between November 2005 and January 2006. Further data were collected from group discussions, key informant survey, and observation. This paper attempts to explore some contradictions between scientific and local knowledge on peri-urban agriculture practices. The farmers have now intensified their production to meet the urban demand. The transition has made the farmers adopting improved farming techniques related to the green revolution over traditional practices. The farmers’ practices demonstrate to some extent a link between scientific and indigenous knowledge. They also realise that the institutional extension support is essential to identify and proper use of agricultural inputs available at the local markets, so that the agriculture production can be achieved in a balanced way. The Geographical Journal of Nepal, Vol. 7, 2009: 15-22